2017
DOI: 10.9779/puje844
|View full text |Cite
|
Sign up to set email alerts
|

Türkiyede Uygulanan Okul Öncesi Eğitim Programında Matematik: Planlama ve Uygulama

Abstract: Bu çalışma, okul öncesi eğitim kurumlarında görev yapan öğretmenlerin programda matematik eğitimini planlama ve uygulama durumlarını incelemek amacıyla yapılmıştır. Araştırmanın evrenini Türkiye'de okul öncesi eğitim kurumlarında görev yapan öğretmenler oluşturmuştur. Araştırmanın çalışma grubuna ulaşılabilir örneklemden 165 öğretmen dahil edilmiştir. Araştırmada genel tarama modeli kullanılmıştır. Veri toplama aracı olarak öğretmenlere ilişkin genel bilgileri toplamak amacıyla "Genel Bilgi Formu" ve Amerika'd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
1
5
0
1
Order By: Relevance
“…The responsibility for making decisions about the method, content, sequence, and intensity of instruction were all given to the teacher. Unfortunately, only a small number of early childhood teachers have adequate education about math instruction or use a comprehensive and researchbased math curriculum (Ginsburg, Lee and Boyd, 2008;Kaçan and Halmatov, 2017). Also, teachers believe that math was not an interesting topic for children (Alat, 2019), and supporting the development of social and emotional skills and early literacy skills is more important than math skills (Kaçan and Halmatov 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responsibility for making decisions about the method, content, sequence, and intensity of instruction were all given to the teacher. Unfortunately, only a small number of early childhood teachers have adequate education about math instruction or use a comprehensive and researchbased math curriculum (Ginsburg, Lee and Boyd, 2008;Kaçan and Halmatov, 2017). Also, teachers believe that math was not an interesting topic for children (Alat, 2019), and supporting the development of social and emotional skills and early literacy skills is more important than math skills (Kaçan and Halmatov 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only a small number of early childhood teachers have adequate education about math instruction or use a comprehensive and researchbased math curriculum (Ginsburg, Lee and Boyd, 2008;Kaçan and Halmatov, 2017). Also, teachers believe that math was not an interesting topic for children (Alat, 2019), and supporting the development of social and emotional skills and early literacy skills is more important than math skills (Kaçan and Halmatov 2017). That is why, systematic, sequential, well-planned, and in-depth math instruction is not in place in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Ulusal ve uluslararası alan yazın incelendiğinde, okul öncesi öğretmenlerinin matematik etkinliklerine ve sınıf içi uygulamalarına ilişkin görüşlerini inceleyen sınırlı sayıda çalışmaya rastlanmıştır (Kılıç ve Özcan, 2020;Koç, 2017;Lo, 2014;Orçan-Kaçan ve Halmatov, 2017;Tantekin-Erden ve Tonga, 2020;Yazlık ve Öngören, 2018). Erken matematik eğitimini geliştirmeyi amaçlayan program geliştiricilerin ve araştırmacıların, okul öncesi öğretmenlerinin erken matematik eğitimine yönelik bakış açılarını dikkate alarak daha fazla önem vermeleri umulmaktadır.…”
Section: Introductionunclassified
“…It is evident that regarding the characteristics of the ideal preschool teacher, his/her supporting and guiding role in ensuring the active participation of children by creating the optimal educational environment is emphasized by the curriculum. The curriculum describes the teacher as not simply an authority who directly transmits information, but as the figure that shows children ways to access information and helps them create their knowledge (Orçan Kaçan & Halmatov, 2017). When planning a math activity, the teacher should offer the children a rich stimulating environment and plan activities that support the active participation of the child.…”
Section: Introductionmentioning
confidence: 99%
“…The current classroom practices indicate that mathematics education activities are planned as learning processes in which mostly the teacher is active and that only the counting skills as a mathematics skill are emphasized with a heavy focus on copying or solving textbook exercises. For example, in their study on how preschool teachers plan and teach the mathematics curriculum, Orçan, Kaçan and Halmatov (2017) found that 82.4% of the teachers considered the counting skills very important.…”
Section: Introductionmentioning
confidence: 99%